Isolation of Helicobacter cinaedi from the Colon, Liver, and Mesenteric Lymph Node of a Rhesus Monkey with Chronic Colitis and Hepatitis - Fox, J. G. (American Society for Microbiology, 2001)
On the basis of biochemical, phenotypic, and 16S rRNA analyses, Helicobacter cinaedi was isolated from the colon, liver, and mesenteric lymph nodes of a 2-year-old rhesus monkey with chronic diarrhea. Histologically, the liver had mild to moderate biliary hyperplasia and hypertrophy with periportal inflammation and fibrosis. Colonic and cecal lesions consisted of diffuse chronic inflammation and glandular hyperplasia extending the length of the crypts. This is the first observation of H. cinaedi associated with active hepatitis and colitis in a nonhuman primate.